Bridging two‐liquid theory with molecular simulations for electrolytes: An investigation of aqueous NaCl solution. Issue 4 (23rd January 2019) - Saravi, Sina H.; Ravichandran, Ashwin; Khare, Rajesh; Chen, Chau‐Chyun
Abstract : We reexamine the theoretical framework of electrolyte nonrandom two‐liquid model and formulate the binary interaction parameters as functions of species diameter ( σ ), effective interaction strength ( ɛ ), the domain radius around the center species ( R ), and the nonrandomness factor ( α ). We show that these quantities can be directly obtained from molecular simulations using aqueous NaCl as the model system. The binary interaction parameters determined from the simulations are consistent with those obtained from regression of experimental data. Our work provides a molecular interpretation of the classical thermodynamic model and shows a way to predict from molecular simulations the binary interaction parameters for use in process industries. © 2019 American Institute of Chemical Engineers AIChE J, 65: 1315–1324, 2019